IN VITRO EVALUATION OF THE ANTITUBERCULOSIS POTENTIAL OF BASIL LEAF ETHANOL EXTRACT USING THE RESAZURIN MICROTITER ASSAY (REMA) METHOD - Setiadi, Nurlina; Lubis, Humairah Medina Liza; Syafina, Ikhfana (Biomedika, 2026)
Background: Tuberculosis (TB) remains a global health challenge and is the second leading infectious cause of death. Indonesia ranks among the top three countries with the highest TB burden. Efforts to discover safer and more effective antituberculosis agents include exploring natural products such as basil (Ocimum basilicum), which contains antimicrobial bioactive compounds. Objective: To determine the minimum inhibitory concentration (MIC) of basil leaf ethanol extract against Mycobacterium tuberculosis H37Rv using the Resazurin Microtiter Assay (REMA). Methods: Basil leaves were extracted by maceration using 96% ethanol and tested at concentrations of 2.5%, 1.25%, and 0.625%. Antimycobacterial activity was evaluated using REMA, with rifampicin as the positive control and untreated media as the negative control. Color change from blue to pink indicated bacterial growth. Results: All concentrations of basil extract produced a pink color, indicating continued bacterial growth, whereas rifampicin remained blue, confirming assay validity. The MIC of the extract was >2.5 µg/mL, indicating no inhibitory effect at the tested concentrations. Conclusion: Basil leaf ethanol extract did not inhibit M. tuberculosis H37Rv at the evaluated doses. Further research using higher concentrations, phytochemical profiling (LC–MS/GC–MS), and fractionation of active compounds is recommended to explore its potential antimycobacterial activity.